Gas extraction operations and livelihood diversification in Tanzania: Rhetoric and reality - Beston Musa Musoma; Suzana Samson Nyanda; Mikidadi Idd Muhanga; Fatihiya Ally Massawe (Heliyon, 2023)
The lives and livelihoods of farming and fishing communities in rural Tanzania are highly susceptible to extractive investment operations. Livelihood diversification in communities beyond agriculture and fishing can be an effective way to cope with the adverse impacts of extractive investment operations. Gas extraction operations (GEOs) are expected to change and diversify communities’ livelihoods. Tanzania has new GEOs; thus, it is necessary to investigate how they have diversified livelihoods in Mtwara Rural District. This article addresses the associations between GEOs and diversifying livelihoods. The paper explores (i) livelihood diversification before and during GEOs, (ii) associations between GEOs and villagers' livelihoods diversification, and (iii) communities' perspectives on GEOs and livelihood diversification. Proportionate stratified sampling was used to obtain 260 respondents. A questionnaire-based survey, four (4) Focus Group Discussions (FGDs), and fifteen (15) Key Informant Interviews (KIIs) were used to collect data. IBM-SPSS version 25 was used to analyse quantitative data. The Chi-square test was employed to analyse livelihood diversification concerning GEOs. Content analysis was used for qualitative data. Near and distant communities saw farming decline by 81.5% and 83.5%, respectively. Also, fishing declined by 85.2% and 83.7%. On the other hand, GEOs enhanced motorbike transport by 160.0% and 300.0%, food vending improved by 166.7% and 236.4%, and seashell collection increased by 816.0% and 462.5%, respectively. GEOs diversified farming (p = 0.001), fishing (p = 0.008), agricultural wage labour (p = 0.000), and crop business (p = 0.036) with moderate strength of association. GEOs have diversified livelihoods in the study area. The study demonstrates that communities surrounding GEOs are highly socioeconomically vulnerable due to GEOs which caused declining agricultural and fish catches, thus negatively affecting their livelihoods. It is recommended that long-term programmes such as the building of diverse agro-based enterprises for job creation, training on income-generating occupations, agribusiness and technical training are required to increase earnings and enhance living standards. Both public and private entities should conduct a targeted and context-specific initiative to increase livelihood diversification among nearby and distant households, which can improve livelihood resilience.